Intracellular localization of the mycobacterial stressosome complex - Malavika Ramesh (Nature Portfolio, 2021)
Abstract Microorganisms survive stresses by alternating the expression of genes suitable for surviving the immediate and present danger and eventually adapt to new conditions. Many bacteria have evolved a multiprotein "molecular machinery" designated the "Stressosome" that integrates different stress signals and activates alternative sigma factors for appropriate downstream responses. We and others have identified orthologs of some of the Bacillus subtilis stressosome components, RsbR, RsbS, RsbT and RsbUVW in several mycobacteria and we have previously reported mutual interactions among the stressosome components RsbR, RsbS, RsbT and RsbUVW from Mycobacterium marinum. Here we provide evidence that "STAS" domains of both RsbR and RsbS are important for establishing the interaction and thus critical for stressosome assembly. Fluorescence microscopy further suggested co-localization of RsbR and RsbS in multiprotein complexes visible as co-localized fluorescent foci distributed at scattered locations in the M. marinum cytoplasm; the number, intensity and distribution of such foci changed in cells under stressed conditions. Finally, we provide bioinformatics data that 17 (of 244) mycobacteria, which lack the RsbRST genes, carry homologs of Bacillus cereus genes rsbK and rsbM indicating the existence of alternative σF activation pathways among mycobacteria.